2015
DOI: 10.1016/j.cbi.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Benzene oxide is a substrate for glutathione S-transferases

Abstract: Benzene is a known human carcinogen which must be activated to benzene oxide (BO) to exert its carcinogenic potential. BO can be detoxified in vivo by reaction with glutathione and excretion in the urine as S-phenylmercapturic acid. This process may be catalyzed by glutathione S-transferases (GSTs), but kinetic data for this reaction have not been published. Therefore, we incubated GSTA1, GSTT1, GSTM1, and GSTP1 with glutathione and BO and quantified the formation of S-phenylglutathione. Kinetic parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
(36 reference statements)
1
16
0
Order By: Relevance
“…While this effect of genotype has been noted before, our study is the largest and most definitive [ 31 40 ]. The stronger effect of GSTT1 than GSTM1 deletion observed here is consistent with our metabolic studies which demonstrate that GSTT1 is a better catalyst of benzene oxide conjugation than GSTM1 [ 54 ]. The size of our study allowed us to analyze ethnic differences in SPMA levels correcting for each genotype.…”
Section: Discussionsupporting
confidence: 92%
“…While this effect of genotype has been noted before, our study is the largest and most definitive [ 31 40 ]. The stronger effect of GSTT1 than GSTM1 deletion observed here is consistent with our metabolic studies which demonstrate that GSTT1 is a better catalyst of benzene oxide conjugation than GSTM1 [ 54 ]. The size of our study allowed us to analyze ethnic differences in SPMA levels correcting for each genotype.…”
Section: Discussionsupporting
confidence: 92%
“…We and others have previously shown that GSTT1 null status has a strong effect on levels of SPMA (26, 27), and that was also observed in this study, where levels of SPMA were significantly lower in GSTT1 null individuals than in non-nulls (Table 3). The 95.4% increase in SPMA in these individuals may be due to PEITC effects on GSTP1 , which is a good catalyst of SPMA formation from benzene oxide (28). GSTP1 is also an excellent catalyst of acrolein and crotonaldehyde conjugation with glutathione (29) and induction of this enzyme may contribute to the effects of PEITC on the urinary levels of HPMA and HMPMA.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled HLC (1 mg) was added to a reaction containing 100 mM potassium phosphate (pH = 7.4) and 250 μ M EXE or 335 μ M 17 β -DHE in a total volume of 1 ml. The reaction mixture was preincubated at 37°C for 3 minutes prior to the addition of 50 µ l of 100 mM GSH (final GSH concentration = 5 mM) ( Lash et al, 1999 ; Zarth et al, 2015 ; Shi et al, 2016 ). After 2 hours at 37°C, the reaction was stopped with an equal reaction volume of ice-cold acetonitrile and centrifuged at 16,100 g for 10 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%